Fluorescent Carbon Nanoparticle Biosensors, Fruits, and Visualization of Latent Fingerprints: Sustainable Forensic Approaches - Kocabas, Alihan; Karakus, Emine (WILEY-V C H VERLAG GMBH, 2025)
Structures referred to as biosensors are defined as devices that provide outputs by converting responses given to a chemical substance. Fluorescent carbon nanoparticles (CNPs), which have high fluorescence efficiency and are increasingly used in biosensors, are group of nanomaterials that exhibit unusual properties compared to normal-sized substances with their high surface areas. Although chemistry progresses every day and new markers are targeted, fingerprints are still among the most commonly used identification tools in forensic cases. Fingerprints are the shapes left on surfaces by papillary protrusions on fingers. Latent fingerprints are traces formed as a result of hands touching objects and/or surfaces, resulting from natural secretions and pollutants coming from the pores of the skin. In our study, biosensors containing fluorescent CNPs synthesized by green synthesis with minimum chemical and energy consumption using hydrothermal reactors from peels of pineapple, mango, orange, and avocado fruits were selected for visualizing latent fingerprints. Nanoparticles characterized by UV, IR, fluorescence spectroscopy, SEM, and XRD analysis. Fingerprints left on aluminum, glass, plastic, treated and untreated wood, paper, steel, and ceramic surfaces were treated by powder and liquid-spray applications. Fingerprints examined under UV light were compared, and the results evaluated whether fingerprints were suitable for identification.
Keywords: Chemistry; Fluorescent carbon nanoparticles; Forensic sciences; Green synthesis; Latent fingerprints